Study of Empowering The 5.0 Educator: A Path Analysis of Digital Leadership and Technological Self-Efficacy Toward Sustainable Educational Excellence - Hernawati W Retno Wiratih; Kasful Anwar; Risnita Risnita; Abdul Halim (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study investigates the psychological drivers of institutional transformation in the Society 5.0 era, specifically within the Indonesian educational landscape of 2022–2026. Titled